2020
DOI: 10.9734/air/2020/v21i130182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-efficacy and Social Support on Intention to Quit Drug Use among People with Drug Abuse Cases

Abstract: Self-efficacy and social support according to various researches have shown to be important factors in the initiation, recognition and enactment of behavioural changes. This study examines the influence of self-efficacy and social support on the intention to quit drug use among clients in some mental health settings and students in a university setting. The sampled participants in this study include 25 students of Ekiti State University, Nigeria and 60 patients drawn from different mental health settings. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…29 The lack of social support, which originates from family, friends, and society, reduces the individual’s resistance to environmental stress and can lead to drug addiction relapse. 6 In a study by Mokuolu and Ajiboye, 7 it was shown that none of the dimensions of social support had a significant relationship with the determination to quit drug abuse, and the result was contrary to the results of the present study.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…29 The lack of social support, which originates from family, friends, and society, reduces the individual’s resistance to environmental stress and can lead to drug addiction relapse. 6 In a study by Mokuolu and Ajiboye, 7 it was shown that none of the dimensions of social support had a significant relationship with the determination to quit drug abuse, and the result was contrary to the results of the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…Perceived social support is the understanding and evaluation of support from family, friends, and others and includes emotional experiences and the creation of attitudes. 5 - 7 Various studies have proved the role of perceived social support in the prevention and treatment of drug abuse and relapse. 8 According to Robb et al, social support for addicted people is associated with increasing their efficiency and reducing their addiction relapse.…”
Section: Introductionmentioning
confidence: 99%
“…According to Locke and Bandura's (1987) social cognitive theory, the treatment of self-efficacy may improve a person's selfesteem, which subsequently contributes to achieving certain goals (Bandura, 2002). Furthermore, it is believed that self-esteem and optimistic behaviour are the key components in examining the extent of motivation a former addict has for recovery during the treatment (Mokuolu & Adedotun, 2020). The more a former addict is confident in normalising his/her behaviour, the higher his/her motivation to recover.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes are reflected as the consequence of constant, general, and intrinsic determiners. Consequently, Mokuolu and Adedotun (2020) indicate that optimism and belief in one's abilities and strengths will update one's behaviour, which he had designated self-esteem. Suppose a person has poor selfesteem, self-efficacy, and optimism, there is a higher risk for the person to suffer from severe depression, which may slow down the recovery process during treatment.…”
Section: Introductionmentioning
confidence: 99%